Definition of Agricultural Management Units in an Inceptisol of the Casanare Department (Colombia) - Ricardo A. Peña - Venegas (Orinoquia, 2013)
Sixty-four representative samples of the 20 cm of shallow soil were taken in an Oxic Dystrudept of the Eastern Mountain Ridge foothills (Casanare, Colombia), on a 58-hectare farm using a nested sampling of four levels. The measured properties correspond to those that determine crop yields. The principal components technique was used for data analysis. Thus, we generated a variable to classify soil with a comprehensive approach called First Principal Component (PC1), which explained 78% of the variation found in the data of the properties that affect specifically crop production. PC1 proved to be a regionalized variable and interpolated via Kriging on the map of the farm. The positive and negative values of this new variable (PC1) determined the UMH for the establishment of commercial crops in the farm.